Challenges with Conventional Dermal Filler Guidelines: Considering Multi-Axes Facial Rotation Asymmetry Patterns - Koppert, Erik; Yi, Kyu-Ho (Archives of plastic surgery, 2025)
Facial asymmetry is inherent from birth, and it becomes more pronounced with age due to changes in the facial skeleton at various rates and locations. As new insights into “multi-axes facial rotation” patterns emerge, there is a pressing need to update the standards for facial assessment, consultation, and treatment to align with modern aesthetic practices. Traditional methods like MD Codes™ and BeautiPHIcation™, which focus on enhancing specific features or applying mathematical beauty principles, may not adequately address overall facial balance and may neglect the underlying skeletal asymmetries that contribute to a person's appearance. These approaches, while innovative, can result in treatments that might not fully appreciate or correct the foundational asymmetries present in the facial skeleton. Therefore, a comprehensive approach that includes a detailed assessment by skilled practitioners is essential to achieve a balanced aesthetic outcome that not only meets individual aesthetic needs but also enhances patient satisfaction through improved education and trust-building between the clinician and the patient.